Blood count suryey of elderly people in the laboratory diagnosis of anemia in private laboratory in Ubiratã – PR (Research, Society and Development, 2022)
The objective of the study was to verify the prevalence of changes in blood counts of the elderly performed in a private laboratory, in the city of Ubiratã - PR, from January to June 2022. This is an exploratory research with a descriptive character of a quantitative approach, performed through the analysis of laboratory reports of blood count of individuals over 60 years of age. The sample result obtained was 1332 reports during the study period. Regarding gender, it was observed that 60% (801 elderly) were female. Of the total, 375 (28.15%) had anemia. The highest prevalence of anemia occurred in males (15.62%) whose age range was 70 to 79 years. A high number of female patients had macrocytosis (39.36%), and a significant number of tests showed anisocytosis (13.59%). Most laboratory tests for anemia of the elderly analyzed remain within the specified reference parameters. Cases of anemia found should not be ignored, because according to the WHO, this portion is high compared to the healthy population.      Keywords: Anemia; Elderly; Blood count; Hemoglobin.